Syntax : - Carnie, Andrew (Wiley-Blackwell, 2013)
Andrew Carnie's bestselling textbook on syntax has guided thousands of students through the discipline of theoretical syntax; retaining its popularity due to its combination of straightforward language, comprehensive coverage, and numerous exercises. In this third edition, topics have been updated, new exercises added, and the online resources have been expanded